The Influence Of Leadership Style, Teamwork And Employee Job Satisfaction On The Performance Of Administrative Employees Of Open Junior High School In Jakarta - Tungga Buana Irfana; Tungga Buana Diana; Aliy Rasyid; Tungga Buana Dharma (Al-Makki Publisher, 2023)
The purpose of this study was to determine the performance of administrative employees at the Open Junior High School (SMP) in Jakarta which was influenced by the principal's leadership style, teamwork and job satisfaction. The method in this study used a survey method in all Open Junior High Schools in Jakarta. The questionnaire distributed 123 to respondents at random. The result of this study is that leadership style has a positive effect on performance, thus, the better the leadership style carried out by the principal, the more it will improve the performance of administrative employees, teamwork has a positive effect on performance. This means that the more compact teamwork will improve the performance of Tata Usha employees, job satisfaction has a positive effect on performance. That is, the higher job satisfaction, the more it will improve the performance of administrative employees, leadership style has a positive effect on job satisfaction. that is, the better the principal's leadership style, the more job satisfaction of administrative employees will be. Teamwork has a positive effect on job satisfaction. This means that the more compact the teamwork, the more it will increase administrative job satisfaction